Shear bond strength of composite bonded with three adhesives to Er,Cr:YSGG laser-prepared enamel - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2010)
Objective: To assess in vitro the shear bond strength of a nanohybrid composite resin bonded with three adhesive systems to enamel surfaces prepared with acid and Er,Cr:YSGG laser etching. Method and Materials: Sixty extracted caries-and restoration-free human maxillary central incisors were used. The teeth were sectioned 2 mm below the cementoenamel junction. The crowns were embedded in autopolymerizing acrylic resin with the labial surfaces facing up. The labial surfaces were prepared with 0.5-mm reduction to receive composite veneers. Thirty specimens were etched with Er,Cr:YSGG laser. This group was also divided into three subgroups, and the following three bonding systems were then applied on the laser groups and the other three unlased groups: (1) 37% phosphoric acid etch + Bond 1 primer/adhesive (Pentron); (2) Nano-bond self-etch primer (Pentron) + Nano-bond adhesive (Pentron); and (3) all-in-one adhesive-single dose (Futurabond NR, Voco). All of the groups were restored with a nanohybrid composite resin (Smile, Pentron). Shear bond strength was measured with a Zwick universal test device with a knife-edge loading head. The data were analyzed with two-factor ANOVA. Results: There were no significant differences in shear bond strength between self-etch primer + adhesive and all-in-one adhesive systems for nonetched and laser-etched enamel groups (P > .05). However, bond strength values for the laser-etched + Bond 1 primer/adhesive group (48.00 +/- 13.86 MPa) were significantly higher than the 37% phosphoric acid + Bond 1 primer/adhesive group (38.95 +/- 20.07 MPa) (P < .05). Conclusion: The Er,Cr:YSGG laser-powered hydrokinetic system etched the enamel surface more effectively than 37% phosphoric acid for subsequent attachment of composite material. (Quintessence Int 2010;41:e119-e124)
Keywords: enamel etching; Er,Cr:YSGG laser; shear bond strength; YAG-LASER; ACID; TENSILE; DENTIN